(untitled) (Sebha University Conference Proceedings, 2025)
Water pollution has been identified as affecting the environmental balance, including the ecosystem. Textile industry has also been identified as a source of wastewater. Depending on the nature of the pollutant, treatment methods such as chemical treatment, physical treatment or biological treatment are selected. Research and development of some cost-effective earth materials for water treatment applications is becoming an important chapter in the modern research world. Clay is the dominant material of the earth, which has versatile properties that are solutions to most of the scientific and technological problems and currently different types of clay are being tested for different water treatment purposes. As part of the present study, it was planned to characterize the chemical properties of three selected clays based on the disclosure of their important properties. The clay samples were collected from three different regions of Sri Lanka and these clays were named as ant nest clay, brick clay and tile clay according to their uses. The clay samples were characterized chemically using X-ray fluorescence (XRF), Fourier transform infrared (FT-IR) spectroscopy and X-ray diffraction (XRD) spectroscopy. According to the study results, each clay contained at least 75% Fe, at most 6% Ti, at most 5.30% Ba, at most 13% K which was present only in ant nest clay and ant nest clay and only 7.5% Ca in brick clay. According to the X-ray fluorescence (XRF) spectroscopy results, the presence of kaolinite, muscovite and quartz as minerals in each clay according to the available associations based on Fourier transform infrared (FT-IR) spectroscopy and mineralogical results was determined. This was confirmed by X-ray diffraction (XRD) spectroscopy results. According to recent research, kaolinite and muscovite are strong adsorbents for some other metals such as heavy metals and dyes and it was also studied that K+ and Ca2+ are strong exchange ions. Therefore, these clays can be recommended for textile wastewater treatment experiments and applications based on the task of removing heavy metals, removing some pathogens, dyes and removing some unnecessary dissolved cations.